High mortality in device-associated infections: a retrospective cohort study from a Brazilian university hospital ICU (2022-2024) - Birbeire Machado, Bruna; Birbeire Machado, Júlia; Ribeiro Manuel, Gabriel; Machado Fonseca, Fernanda (Acta Biologica Brasiliensia, 2026)
This study evaluated the clinical impact, microbiological profile, antimicrobial resistance patterns, and clinical outcomes of healthcare-associated infections (HAIs) in intensive care units (ICUs) of a tertiary Brazilian university hospital. This retrospective observational study included adult patients admitted to the Adult, Coronary, and Neurological ICUs between 2022 and 2024 who developed bacterial HAIs from the third day of hospitalization onward. Epidemiological, microbiological, and outcome data were obtained from institutional surveillance systems. Associations between clinical variables and outcomes were assessed using nonparametric tests, chi-square or Fisher’s exact tests, and Poisson regression. A total of 429 patients developed 656 HAI episodes. Device-associated infections predominated, particularly ventilator-associated pneumonia (34.8%), bloodstream infections (17.5%), and urinary tract infections (17.1%). Overall in-hospital mortality was 54.5% and was independently associated with increasing age. Gram-negative bacteria were the most frequent pathogens, especially Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli. Among K. pneumoniae, 48.9% were ESBL producers and 22.3% were KPC producers. Although resistant phenotypes showed numerically higher mortality, no independent association was observed after adjustment. Device-associated infections impose a substantial burden in ICUs and are predominantly caused by Gram-negative pathogens with relevant resistance patterns observed specifically in organisms such as K. pneumoniae. The high mortality observed appears to be primarily associated with patient-related factors such as age, rather than antimicrobial resistance alone.